2016
DOI: 10.1515/polyeng-2015-0533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the matrix plasticization behavior on mechanical properties of PVC/ABS blends

Abstract: Abstract Acrylonitrile-butadiene-styrene (ABS) grafted copolymer prepared by emulsion polymerization was used to modify different molecular weight poly (vinyl chloride) (PVC) resins. The effects of the molecular weight of the PVC resins on dynamic mechanical analyses (DMA) of PVC/ABS blends and matrix plasticizing behavior on the impact mechanical properties and the morphology were investigated. The tan δ peaks of PVC/ABS blends occurred at the same temperature obtained by DMA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Figure 6 showed that BNT inclusions caused shifting of TGA curve of ABS to right side which indicates the enhancement of thermal stability of pristine ABS. Similar findings were observed in the literature that minerals led to increase for degradation temperature of ABS (Xia et al , 2007; Liu et al , 2016; Savas et al , 2019; He et al , 2010). The highest improvement on thermal stability was observed for 15 Wt.% BNT containing composite.…”
Section: Resultssupporting
confidence: 91%
“…Figure 6 showed that BNT inclusions caused shifting of TGA curve of ABS to right side which indicates the enhancement of thermal stability of pristine ABS. Similar findings were observed in the literature that minerals led to increase for degradation temperature of ABS (Xia et al , 2007; Liu et al , 2016; Savas et al , 2019; He et al , 2010). The highest improvement on thermal stability was observed for 15 Wt.% BNT containing composite.…”
Section: Resultssupporting
confidence: 91%
“…Core‐shell structure modifiers, such as methacrylate‐butadiene‐styrene terpolymer (MBS), core‐shell acrylate elastomer and acrylonitrile‐butadiene‐styrene terpolymer are distributed in PVC in the form of particles 10–13 . Core‐shell structured particles, which comprise rubbery core and rigid shells, have the distinct advantage of allowing independent control of the composition, morphology, size and properties 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Core-shell structure modifiers, such as methacrylatebutadiene-styrene terpolymer (MBS), core-shell acrylate elastomer and acrylonitrile-butadiene-styrene terpolymer are distributed in PVC in the form of particles. [10][11][12][13] Coreshell structured particles, which comprise rubbery core and rigid shells, have the distinct advantage of allowing independent control of the composition, morphology, size and properties. 10 When the PVC is impacted, these particles rupture and form holes, which can lead to stress concentration and induce a large number of crazes and shear bands to consume impact energy.…”
Section: Introductionmentioning
confidence: 99%